Promoting Geographical Imagination through Integrating a Studio Habits of Mind (SHoM) Framework into Pre-Service Primary Teacher Education - Dolan, Anne M.; Morrin, Anne-Marie; Ryan, Sandra (Journal of Geography Education, 2024)
Geographical topics are cross-curricular in nature. Cross curricular teaching in primary schools needs to be supported by interdisciplinary explorations during teacher education programs. This article outlines an interdisciplinary collaboration between three lecturers from Geography, Sociology and Visual Arts. Adapting the Studio Habits of Mind framework (Hetland et al., 2013), this interdisciplinary framework offers an innovative, engaging and creative model of collaboration for lecturers and students in disparate disciplines. The framework is informed by enquiry, constructivism, geographical imagination, and problembased learning and encourages students to adopt flexible, intuitive, and creative strategies to become interdisciplinary innovators, equipped to shape the future of our world.